THE DYNAMICS OF MOTOR SYMPTOMS IN PARKINSON’S DISEASE UNDER THE INFLUENCE OF TRANSCRANIAL MAGNETIC STIMULATION - Sardorbek A. Alixonov; Malika M. Raimova (Central Asian Journal of Medicine, 2024)
Parkinson’s disease (PD) is a chronic, progressive neurodegenerative disorder characterized clinically by a combination of hypokinesia, muscle rigidity, and resting tremors. In other cases, it presents with progressively worsening postural instability, and a variety of non-motor symptoms, such as autonomic dysfunction, affective and cognitive symptoms, and sleep disturbances [4]. Globally, the prevalence of PD (age-dependent) is approximately 1%. The disease typically occurs between the ages of 60 and 65, but in 15% of cases, it can occur before the age of 40. There are also gender differences: men are 1.5 times more likely to develop the disease compared to women [4]. The risk of developing the disease increases with age; thus, after the age of 65, the incidence rate is about 1%.